Peanut oral immunotherapy results in increased antigen-induced regulatory T-cell function and hypomethylation of forkhead box protein 3 (FOXP3) - Syed, Aleena; Garcia, Marco A.; Lyu, Shu-Chen; Bucayu, Robert; Kohli, Arunima; Ishida, Satoru; Berglund, Jelena P.; Tsai, Mindy; Maecker, Holden; O’Riordan, Gerri; Galli, Stephen J.; Nadeau, Kari C. (Journal of allergy and clinical immunology, 2014)
The mechanisms contributing to clinical immune tolerance remain incompletely understood. This study provides evidence for specific immune mechanisms that are associated with a model of operationally defined clinical tolerance. Our overall objective was to study laboratory changes associated with clinical immune tolerance in antigen-induced T cells, basophils, and antibodies in subjects undergoing oral immunotherapy (OIT) for peanut allergy. In a phase 1 single-site study, we studied participants (n = 23) undergoing peanut OIT and compared them with age-matched allergic control subjects (n = 20) undergoing standard of care (abstaining from peanut) for 24 months. Participants were operationally defined as clinically immune tolerant (IT) if they had no detectable allergic reactions to a peanut oral food challenge after 3 months of therapy withdrawal (IT, n = 7), whereas those who had an allergic reaction were categorized as nontolerant (NT; n = 13). Antibody and basophil activation measurements did not statistically differentiate between NT versus IT participants. However, T-cell function and demethylation of forkhead box protein 3 (FOXP3) CpG sites in antigen-induced regulatory T cells were significantly different between IT versus NT participants. When IT participants were withdrawn from peanut therapy for an additional 3 months (total of 6 months), only 3 participants remained classified as IT participants, and 4 participants regained sensitivity along with increased methylation of FOXP3 CpG sites in antigen-induced regulatory T cells. In summary, modifications at the DNA level of antigen-induced T-cell subsets might be predictive of a state of operationally defined clinical immune tolerance during peanut OIT.